FENOMENA BELANJA ONLINE BERLEBIHAN DI KALANGAN GEN Z MUSLIM: ANALISIS PRINSIP KONSUMSI ISLAMI - Afifatunnada Nada; Cory Vidiati (POLITEKNIK PIKSI GANESHA, 2025)
ABSTRACT The growing phenomenon of online shopping among Generation Z Muslims signals a major shift in consumption patterns in the digital age. The purpose of this study is to analyze the excessive online shopping behavior (binge drinking) of Generation Z Muslims based on the principles of Islamic consumption, namely Israf (excessiveness), Tabjir (spending), and Maslaha (profit). The approach used is descriptive and qualitative, with data collection methods through interviews with 12 Muslim students who actively shop on e-commerce platforms such as Shopee, TikTok Shop, and Tokopedia. The results show that accessibility, promotions, and the influence of influencers are key factors that determine consumer behavior. However, some respondents also stated that they consciously apply the values of “qana'ah” (sufficiency) and “tawazun” (balance) to control their shopping behavior. From an Islamic economic perspective, excessive consumption violates the principles of goodness and efficiency of wealth, while balanced consumption reflects compliance with Sharia teachings. This study highlights the importance of financial literacy and spiritual development in accordance with Sharia law so that the younger generation can adopt wise and ethical consumption patterns in the digital age.